Exact solutions of an equation of gas dynamics - Barannyk, Anatoliy; Yuryk, Ivan (My University, 1998)
Anew class of exact solutions of the gas dynamics equations is obtained.
Keywords: gas dynamics equation; рівняння газової динаміки; exact solutions; точні розв'язки; кафедра вищої математики імені проф. Можара В. І.